IMPLEMENTASI KEBIJAKAN PROGRAM WAJIB BELAJAR 9 TAHUN SIDOARJO JAWA TIMUR - Anggraini, Alfi Febrilia; Rajikan; Anggraeny puspanintyas (Madika: Jurnal Politik dan Governance, 2023)
in general, this research has been able to answer the research objectives based on the results of the research and discussion that have been described previously, it can be concluded as follows: The implementation of the 9-year compulsory education policy has been going as desired, it's just that the implementation of compulsory education has not been optimal according to what is desired because there is one indicator that has not been said to be optimal in terms of communication, due to socialization carried out by the District Education Office Sidoarjo has not been optimal for the community, so that many people and some teachers do not understand the 9-year compulsory education policy held by the Sidoarjo Regency Government In general, this research has been able to answer the research objectives based on the results of the research and discussion that have been described previously, it can be concluded as follows: The implementation of the 9-year compulsory education policy has been going as desired, it's just that the implementation of compulsory education has not been optimal according to what is desired because there is one indicator that has not been said to be optimal in terms of communication, due to socialization carried out by the District Education Office Sidoarjo has not been optimal for the community, so that many people and some teachers do not understand the 9-year compulsory education policy held by the Sidoarjo Regency Government.